Community-Based Mental Health Education in Empowering People with Mental Disorders in the Community - Damayanti, Rika; Abdulhak, Ishak; Hatimah, Ihat; S. Ardiwinata, Jajat (International Journal of Psychosocial Rehabilitation, 2020)
The increasing numbers of mental disorders demand a mental health paradigm change from hospital-based services to community-based services. The community has an important role in contributing to both the healing and recurrence of clients with mental disorders in the community. Unfortunately, not all people have mental health literacy. Thus, the community-based education aspects should be a priority in promoting, preventing, curing, and rehabilitating efforts. The purpose of this study was to determine the effect of community-based mental health education in increasing knowledge and empowering clients with mental disorders in the community. This research employed the quantitative method with a post-test design of a quasi-experimental approach. The purposive sampling was used to determine the sample, which consisted of 10 people in the experimental group and 10 people in the control group. The data was collected through questionnaires and observation by referring to the empowerment index proposed by Schuler, Riley, and Hashemi. Interventions for the experimental group were in the form of mental health education through home visits and group meetings by involving those responsible for mental health, health centers, families, and mental health cadres. The interventions for the control group were in the form of mental health education through home visits using leaflet media. The results showed an increase in cognitive abilities and the level of client empowerment after treatment, both in the experimental group (p-value of 0.036 and 0.015) and the control group (p-value of 0.041 and 0.048). It is recommended for mental health service providers in the community to carry out mental health education activities continuously through partnerships with government institutions, private professional organizations, and the community in socializing the mental health problems and increasing the empowerment of clients with mental disorders in all aspects of life.